A larger critical shoulder angle requires more rotator cuff activity to preserve joint stability. Issue 6 (29th December 2015) - Viehöfer, Arnd F.; Gerber, Christian; Favre, Philippe; Bachmann, Elias; Snedeker, Jess G.
ABSTRACT: Shoulders with rotator cuff tears (RCT) tears are associated with significantly larger critical shoulder angles (CSA) (RCT CSA = 38.2°) than shoulders without RCT (CSA = 32.9°). We hypothesized that larger CSAs increase the ratio of glenohumeral joint shear to joint compression forces, requiring substantially increased compensatory supraspinatus loads to stabilize the arm in abduction. A previously established three dimensional (3D) finite element (FE) model was used. Two acromion shapes mimicked the mean CSA of 38.2° found in patients with RCT and that of a normal CSA (32.9°). In a first step, the moment arms for each muscle segment were obtained for 21 different thoracohumeral abduction angles to simulate a quasi‐static abduction in the scapular plane. In a second step, the muscle forces were calculated by minimizing the range of muscle stresses able to compensate an external joint moment caused by the arm weight. If the joint became unstable, additional force was applied by the rotator cuff muscles to restore joint stability. The model showed a higher joint shear to joint compressive force for the RCT CSA (38.2°) for thoracohumeral abduction angles between 40° and 90° with a peak difference of 23% at 50° of abduction. To achieve stability in this case additional rotator cuff forces exceeding physiological values were required. Our results document that a higher CSA tends to destabilize the glenohumeral joint such that higher than normal supraspinatus forces are required to maintain modeled stability during active abduction. This lends strong support to the concept that a high CSA can induce supraspinatus (SSP) overload. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:961–968, 2016.